A Case Report of Echinococcus granulosus sensu stricto (G1) in a Domestic Cat in Turkey - OGUZ, B; SELCIN, O; DEGER, MS; BICEK, K; OZDAL, N (Journal of the Hellenic Veterinary Medical Society, 2022)
Echinococcus granulosus sensu lato is a zoonotic helminth with a life cycle that include of definitive hosts (dogs and wild carnivores) and intermediate hosts (usually the even-toed ungulates, Artiodactyla). Intermediate hosts become infected by ingesting the parasite eggs in contaminated food and water. Accidental intermediate hosts acquire infection in a similar way as other intermediate hosts. A two-year-old female cat was presented to the Van (Turkey) Animal Care and Rehabilitation Center with abdominal tension. Multiple intraperitoneal vesicles, which were found to be E. granulosus (s.1.) metacestodes, were observed during the ultrasound imaging. Then, the animal was laparotomized. Phylogenetic analysis based the partial cytochrome c oxidase 1 (pcox1) mitochondrial gene region was performed on metacestode samples (hydatid cysts). The isolate was identified as sensu stricto genotype G1, which is most commonly found in Turkey.